Perancangan Sistem Penjualan Digital Menggunakan Metode Prototype dan Evaluasi Kualitas Berdasarkan ISO/IEC 25010 pada PT Snapdev Digital Indonesia - Putri Khoiriah Harahap; Sinta Mutiara; Chairul Anwar (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The rapid development of information technology has encouraged companies to switch from conventional sales systems to digital-based systems in order to improve operational efficiency and service quality. PT Snapdev Digital Indonesia still uses a manual sales management system, causing problems such as inaccurate data recording, difficulty in monitoring transactions in real-time, and lack of integration between business processes. This study aims to design a digital sales system using the Prototype method and evaluate its quality based on the ISO/IEC 25010 standard. A mixed method approach was applied through qualitative data collection (observation, interviews, and documentation) and quantitative analysis through system quality testing. System modeling using UML includes Use Case Diagram, Activity Diagram, Sequence Diagram, and Class Diagram. The system is implemented on a web-based platform using a MySQL database. ISO/IEC 25010 testing results indicate Functional Suitability (94.5%), Usability (91.2%), Performance Efficiency (89.7%), Reliability (92.3%), and Security (90.1%), with an overall average of 91.6% categorized as Very Good.